Peningkatan Kemampuan Mendengarkan (Listening) Mahasiswa Bahasa Inggris Melalui Model Pembelajaran “Project-Based Learning” - Yulia Nur Ekawati (Cakrawala: Jurnal Pendidikan, 2017)
The importance of mastering the listening skill in learning foreign language (English) requires the lecturer’s role to implement the enjoyable, applicative and interactive teaching and learning. Based on the previous studies, ProjectBased Learning (PBL) model can improve students’ listening and speaking skills. This research, therefore, aims to find out: (a) how students and lecturer learning activities implement Project-Based Learning in Listening class, and (b) to what extend the students’ listening achievement through this Project-Based Learning model. The sample is third semester students at English education department of Teacher and Training Faculty of Pancasakti University of Tegal on the subject of Listening in Professional Contexts. To obtain the data, researcher uses action research with two cycles. There are four stages on each cycle, i.e: Planning, Implemetation of Action, Observation and Evaluation, as well as Reflection. After gaining data and conducting analysis, the result, furthermeore, contributes in Listening class, in which it can be shown through increasing students’ achievement and applying this model